2020
DOI: 10.33594/000000222
|View full text |Cite
|
Sign up to set email alerts
|

4,4'-Diisothiocyanato-2,2'-Stilbenedisulfonic Acid (DIDS) Modulates the Activity of KCNQ1/KCNE1 Channels by an Interaction with the Central Pore Region

Abstract: This article is licensed under the Creative Commons Attribution-NonCommercial-NoDerivatives 4.0 International License (CC BY-NC-ND). Usage and distribution for commercial purposes as well as any distribution of modified material requires written permission.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 37 publications
1
1
0
Order By: Relevance
“…Initially, we examined the effect of DIDS on WT EQ. Consistent with previous studies ( Abitbol et al, 1999 ; Bollmann et al, 2020 ) we confirmed that 100 µM DIDS enhanced WT EQ activity ( Figure 5B ) with a V 1/2 shift of –46.6 mV and a decrease in the slope of the G-V curve ( Table 5 ). As most I Ks activators are dependent on the KCNQ1-KCNE1 stoichiometry, this more potent effect of DIDS seen in our study may be explained by the higher dose we used and our KCNE1-KCNQ1 linked channel constructs, which ensured fully KCNE1-saturated complexes.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Initially, we examined the effect of DIDS on WT EQ. Consistent with previous studies ( Abitbol et al, 1999 ; Bollmann et al, 2020 ) we confirmed that 100 µM DIDS enhanced WT EQ activity ( Figure 5B ) with a V 1/2 shift of –46.6 mV and a decrease in the slope of the G-V curve ( Table 5 ). As most I Ks activators are dependent on the KCNQ1-KCNE1 stoichiometry, this more potent effect of DIDS seen in our study may be explained by the higher dose we used and our KCNE1-KCNQ1 linked channel constructs, which ensured fully KCNE1-saturated complexes.…”
Section: Discussionsupporting
confidence: 92%
“…To establish whether the binding pocket for mefenamic acid can be generalized to other I Ks activators, we also examined the binding of the structurally unrelated I Ks activator, DIDS. Stilbenes such as DIDS ( Figure 5A ) also activate I Ks ( Abitbol et al, 1999 ; Bollmann et al, 2020 ), and given their molecular differences from fenamates, it is of interest to explore common structural and dynamic features of their binding to the I Ks channel complex. 100 µM DIDS had no effect on endogenous currents in GFP-transfected tsA201 cells but treatment of WT EQ channels with 100 µM DIDS transformed the slowly activating waveform into one with faster onset (although not instantaneous like mefenamic acid) and inhibited tail current decay ( Figure 5B ).…”
Section: Resultsmentioning
confidence: 99%